Environmental Conference at CEU - Tisza
Recording of the coverage made by Duna Televízió about the international conference entitled "Rivers of Life or Rivers of Death? Transboundary Environmental Issues in Central and Eastern Europe" held at CEU and hosted by the CEU Department of Environmental Sciences and Policy. The central theme of the conference was water pollution, particularly the level of pollution of the river Tisza. The coverage contains a short interview with Illés Zoltán, Associate Professor at CEU, Department of Environmental Sciences and Policy.